2017
DOI: 10.1109/tro.2016.2623339
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Elastic Rods With a Robot-Manipulated Magnet for Medical Applications

Abstract: Magnet-tipped, elastic rods can be steered by an external magnetic field to perform surgical tasks. Such rods could be useful for a range of new medical applications because they do not require either pull wires or other bulky mechanisms that are problematic in small anatomical regions. However, current magnetic rod steering systems are large and expensive. Here, we describe a method to guide a rod using a robot-manipulated magnet located near a patient. We solve for rod deflections by combining permanent-magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 27 publications
0
63
0
Order By: Relevance
“…Bevel‐tip needle steering is driven by asymmetric tip geometry resulting in a net lateral force upon insertion in soft media that leads to a curved insertion trajectory . Asymmetric tip geometry can be a simple bevel or a more complex bent tip, both of which can be guided by closed‐loop control over implant position via needle rotation or magnetic actuation . These techniques have not, however, been put into clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…Bevel‐tip needle steering is driven by asymmetric tip geometry resulting in a net lateral force upon insertion in soft media that leads to a curved insertion trajectory . Asymmetric tip geometry can be a simple bevel or a more complex bent tip, both of which can be guided by closed‐loop control over implant position via needle rotation or magnetic actuation . These techniques have not, however, been put into clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…Results from this study showed decreased radiation exposure and safe and effective procedures [43]. Furthermore, Kratchman et al [32] demonstrated the guidance of a magnet-tipped rod along arbitrary 3-D trajectories using a single, robot-manipulated permanent magnet. The magnet was attached to a 6-DoF serial robot, which demonstrated trajectory following and obstacle avoidance using resolved-rate motion control.…”
Section: Passive Magnetic Actuationmentioning
confidence: 78%
“…Consequently, accurate mechanical models and continuous device localization are specific fundamental requirements of control strategies for magnetic catheter actuation [74]. Mechanical models used for accurately describing the system and environment include Euler-Bernoulli beam deflection [35], rigid link approximation [75], the Cosserat rod theory [32], and pseudorigid body modeling [76]. The localization of catheters has been demonstrated by accurately using electromagnetic tracking [27] and by observing the device shape and orientation using MR, US, and fluoroscopy.…”
Section: Control Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…physical point where robot is at least partially constrained, and applied loads [9]- [12]. Similar methods have been applied for continuum devices that rely on magnetic fields for actuation [5], [6], [13].…”
Section: Introductionmentioning
confidence: 99%